2020
DOI: 10.1177/0194599820934748
|View full text |Cite
|
Sign up to set email alerts
|

Otopathologic Analysis of Patterns of Postmeningitis Labyrinthitis Ossificans

Abstract: Objective Labyrinthitis ossificans (LO) may occur following meningitis and, in cases where cochlear implantation is indicated, complicate electrode insertion. LO is critical to identify for successful cochlear implantation, and histopathology is more sensitive than imaging for identification of LO. Herein we utilize otopathologic techniques to study the timing and location of intracochlear tissue formation following meningitic labyrinthitis (ML). Study Design Retrospective review. Setting Academic institution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…All TL samples exhibited varying degrees of CO at various locations within the cochlea, most commonly at the basal turn, without a particular predilection for endolymph versus perilymph. Animal and human models have shown that fibrosis and ossification after bacterial meningitis tend to start most at the area of the round window in the scala tympani via infiltration of proinflammatory cytokines through the cochlear aqueduct and progress from the basal turn 12 The pattern of ossification seen after TL surgery may reflect this pattern as the basal turn was involved in all ossified samples. Only one case from the RS or MF samples showed ossification.…”
Section: Discussionmentioning
confidence: 99%
“…All TL samples exhibited varying degrees of CO at various locations within the cochlea, most commonly at the basal turn, without a particular predilection for endolymph versus perilymph. Animal and human models have shown that fibrosis and ossification after bacterial meningitis tend to start most at the area of the round window in the scala tympani via infiltration of proinflammatory cytokines through the cochlear aqueduct and progress from the basal turn 12 The pattern of ossification seen after TL surgery may reflect this pattern as the basal turn was involved in all ossified samples. Only one case from the RS or MF samples showed ossification.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies indicate that the sequence of events in labyrinthitis ossificans begins with inflammation that progresses to fibrosis and ossification, and further that ossification of the cochlear can continue over the years [12,13]. Histopathological analysis of temporal bone specimens has demonstrated that fibrosis can be identified as early as 1.5 weeks after meningitic labyrinthitis [14]. Labyrinthitis ossificans presents several intraoperative challenges for the CI surgeon, precluding electrode insertion via a round window or cochleostomy approach and requiring drilling of the cochlear basal turn or the use of a split electrode array [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Post-operative outcomes in CI recipients are more variable in patients with labyrinthitis ossificans. While audiologic outcomes can be adequate in the setting of cochlear fibrosis and ossification, the timing of implantation may influence postoperative outcomes [ 14 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from visualizing normal cochlear walls, OCT imaging has the potential to detect other obstacles on the insertion path, such as pathological fibrosis and ossification of the ST. This is particularly important in patients who have previously undergone CI surgery 44 , 45 , in patients with cochlear otosclerosis 46 and when cochlear hearing loss is related to a meningitis infection 47 . In patients with these pathologies, the outcome can often be complicated by incomplete electrode insertions, electrode translocations and device failures 46 .…”
Section: Discussionmentioning
confidence: 99%
“…In patients with these pathologies, the outcome can often be complicated by incomplete electrode insertions, electrode translocations and device failures 46 . Furthermore, the cochlear obstruction is often not clearly visible on preoperative imaging, increasing the risk of complications 47 . OCT-guided insertion could help the surgeon estimate the risk of obstruction intraoperatively and decide whether the obstacle can be bypassed by adjusting the insertion trajectory or if an alternative insertion route is necessary (e.g.…”
Section: Discussionmentioning
confidence: 99%